Heterogeneous foldamers from aliphatic-aromatic amino acid building blocks: current trends and future prospects - Nair, Roshna V.; Vijayadas, Kuruppanthara N.; Roy, Arup; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2014)
Chemists' constant pursuit of understanding of the underlying principles of nature's most intricate phenomenon such as protein folding has led to the development of the field of foldamers. The emergence of diverse classes of unnatural amino acid building blocks has unleashed countless opportunities to design, develop and explore the structural and functional aspects of synthetic peptides. One current trend in foldamer chemistry is the heterofoldamer approach, which involves systematic stoichiometric variation of various natural/unnatural amino acid residues, leading to conformational ordering with intriguing structural architectures. In this regard, the incorporation of aromatic amino acids provides efficient structural rigidification and tunability to the molecular scaffolds, which can exhibit a range of secondary structural features. Recent times have witnessed an upsurge of foldamers featuring aliphatic-aromatic residues with diverse structural propensities. This review is an effort to cover this rapidly developing field of foldamer science and also to envisage its future perspectives.
Keywords: Amino acids; Conformation analysis; Foldamers; hydrogen bonding; Peptides; Stacking interactions